2016
DOI: 10.1101/050856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging decision-related neural cascades in the human brain

Abstract: 20Perceptual decisions depend on coordinated patterns of neural activity cascading across 21 the brain, running in time from stimulus to response and in space from primary sensory 22 regions to the frontal lobe. Measuring this cascade and how it flows through the brain is 23 key to developing an understanding of how our brains function. However observing, let 24 alone understanding, this cascade, particularly in humans, is challenging. Here, we report 25 a significant methodological advance allowing this obser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…The majority of these studies, however, used indirect stimulus- or model-derived correlates of EA that do not necessarily reflect endogenous trial-by-trial variability in information processing, which has been shown to offer additional explanatory power in analysing functional brain imaging data and exposing latent brain states234344.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies, however, used indirect stimulus- or model-derived correlates of EA that do not necessarily reflect endogenous trial-by-trial variability in information processing, which has been shown to offer additional explanatory power in analysing functional brain imaging data and exposing latent brain states234344.…”
Section: Discussionmentioning
confidence: 99%
“…Recent modelling and stand-alone fMRI studies have made significant progress in establishing a link between value-based decisions and an accumulation-to-bound mechanism 16 26 27 40 41 42 . The majority of these studies, however, used indirect stimulus- or model-derived correlates of EA that do not necessarily reflect endogenous trial-by-trial variability in information processing, which has been shown to offer additional explanatory power in analysing functional brain imaging data and exposing latent brain states 23 43 44 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the RTs reflect, in addition to perceptual discriminability, cognitive processes related to decision making, attention and response preparation. The decision making cascade involves several brain areas and components with different temporal dynamics (Philiastides et al 2014;Muraskin et al 2016). The top-down attention and response control components found in our discrimination analysis likely involve processes related also to decision making.…”
Section: Discussionmentioning
confidence: 99%